Highly dispersed copper-based nanocomposite synthesis via spray pyrolysis: towards waste-to-hydrogen production through the water-gas shift reaction - Jeon, I. Jeong; Lee, Jae Seob; Baek, Kun Woo; Kim, Chang Hyeon; Gong, Ji Hyeon; Jang, Won Jun; Cho, Jung Sang; Shim, Jae Oh (Journal of Materials Chemistry A, 2024)
In this study, we synthesized a Cu-ZrCeO2 catalyst using spray pyrolysis, which exhibited high activity, stability, and reusability at high temperatures. The catalyst was applied to a high-temperature water-gas shift reaction under practical conditions using waste-derived synthesis gas. Various reducible supports, including CeO2, ZrO2, TiO2, ZrCeO2, and TiCeO2 were evaluated. Among these, the Cu-ZrCeO2 (SPCZC) catalyst exhibited the highest activity and stability, attributed to its abundant oxygen defects, high Cu dispersion, and significant oxygen storage capacity. The SPCZC catalyst achieved 76% CO conversion and 100% CO2 selectivity at 400 °C. It also maintained stable catalytic performance for 50 h, showing resistance to Cu sintering and preservation of the yolk-shell structure, indicating high reusability. A comprehensive deactivation study was conducted on the catalysts. Rapid Cu sintering was observed when CeO2 was used as the sole support, leading to the breakdown of the yolk-shell structure. Catalysts supported on ZrO2, TiO2, and TiCeO2 also experienced Cu sintering and carbon deposition, leading to deactivation.
Keywords: Copper-based; Gas shift reaction; High activity; Highest temperature; Nanocomposite synthesis; Synthesised; TiO 2; Water-gas shifts; Yolk-shell structures; ]+ catalyst